From Seminar to University: Dismantling an Old and Constructing a New Teacher Education in Finland and Sweden, 1946–1979 - Furuhagen, Björn; Holmén, Janne (Nordic Journal of Educational History, 2017)
In the 1970s, Sweden and Finland abandoned the system of seminars for folk school teachers and incorporated all teacher education into the system of higher education. The visions behind the new education, as well as the original plans for its structure, were similar in both countries, but the outcomes were different. Finland managed to a greater extent to implement an academic teacher education located at universities, while the Swedish solution was deemed unsatisfactory by many actors, leading to several new reforms in the following decades. This can be explained by the different nature of the conflicts surrounding the reforms in Sweden and Finland. In Finland, the early 1970s was a period of intense left-right polarisation, followed by attempts to depoliticise teacher education. In Sweden, the vision of an academic teacher education met successful resistance from regional actors, resulting in the preservation of much of the old seminar system under the guise of small teacher education colleges.